GLACIAL-INTERGLACIAL VARIABILITY IN THE DELIVERY OF DUST TO THE CENTRAL EQUATORIAL PACIFIC OCEAN - Anderson R.F.; Fleisher M.Q.; Lao Y. (My University, 2006)
Fluxes of continental mineral aerosols (dust) were greater during glacial periods than during interglacials throughout most regions of the Earth. The equatorial Pacific Ocean was a possible exception to this pattern in that previous studies have reported either greater dust fluxes during interglacials or no consistent glacial–interglacial pattern of dust flux. We have applied the 230Th-normalization technique to derive five new records of dust flux from central equatorial Pacific Ocean sediments. In contrast to previous studies, which relied on stratigraphic accumulation rates, the 230Th-normalization technique produces internally consistent results, revealing fluxes to this region of continental lithogenic material that were positively correlated with global ice volume throughout the past 300,000 yr. Maximum glacial fluxes of continental mineral aerosols exceed minimum interglacial fluxes by about a factor of 2, similar to changes found elsewhere at low and mid-latitudes. This amplitude of variability is substantially smaller than that seen in some recent models, and these observations provide a calibration point for future model development.
Keywords: equatorial Pacific; mineral aerosols; dust; sediment focusing